The Role of 25-Hydroxyvitamin D as a Predictor of Clinical and Radiological Outcomes in Early Onset Rheumatoid Arthritis - Quintana-Duque, Mario Andrés; Caminos, Jorge Eduardo; Varela-Nariño, Adriana; Calvo-Paramo, Enrique; Yunis, Juan José; Iglesias-Gamarra, Antonio (Journal of clinical rheumatology, 2017)
The aims of this study were to compare the levels of 25-hydroxyvitamin D (25(OH)D) in patients with early-onset rheumatoid arthritis (EORA) versus a healthy control group and to assess the association of 25(OH)D deficiency and the BsmI polymorphism of the vitamin D receptor gene with clinical, radiological, and laboratory parameters. Early-onset RA Colombian patients were enrolled in a 3-year follow-up study. Vitamin D deficiency was diagnosed for 25(OH)D levels of less than 20 ng/mL. Pearson and Spearman correlation coefficients were used to assess data. Seventy patients and 70 matched healthy subjects were included. 25-Hydroxyvitamin D was lower in the EORA group (27.13 [SD, 13.4] ng/mL vs. 33.74 [SD, 16.7] ng/mL; P = 0.01); 31.4% of EORA patients were vitamin D deficient. Remission was higher in subjects without 25(OH)D deficiency (22.7% vs. 47.9%; P = 0.04). Patients with 25(OH)D deficiency at baseline had higher Health Assessment Questionnaire and Physician Global Disease Activity Assessment scores, fatigue levels, erythrocyte sedimentation rate, and morning stiffness after 3 years. At disease onset, only a relationship between 25(OH)D deficiency with fatigue and morning stiffness was found. Neither radiographic progression nor Sharp van der-Heidje score was associated to hypovitaminosis D after 36-month follow-up. The bb genotype was less frequent in patients with vitamin D deficiency (0% vs. 16.6%; P = 0.04). Patients with BB-Bb genotype had lower 25(OH)D and a propensity to more severe disease. Our data provide further support for a role of vitamin D as a clinical biomarker for RA. Baseline 25(OH)D could have potential as a predictor of disease severity in EORA.